Complex parts surface modelling from laser scanning data - Abd Manaf, Ismanizam; Ismail, Napsiah; Hamouda, Abdel Magid Salem; Wong, Shaw Voon (2005)
This paper presents the application of non-contact digitizing method for reverse engineering purposes. The 3D scanner with Cyberware CyDir scanning software was used in this research. Five modules are proposed namely i) linear scan mode and angle ii) scanning methods with proper orientation iii) scanning through surfaces iv) cloud points merge and polygonal mesh and v) editing. The output results of data scanned are also discussed. The advantages of this method are also highlighted.